The Influence of Pregnant Women's Knowledge Level on Early Detection of Preeclampsia - Darwati, Lilik (Universitas STRADA Indonesia, 2024)
Pregnancy is a physiological condition that can be followed by pathological processes that threaten the condition of the mother and fetus. The aim is to analyze the level of knowledge of pregnant women regarding early detection of preeclampsia. The research method used was observational analysis with a cross sectional approach collected at a certain time simultaneously. The research population was all 33 pregnant women. The sample size is known by looking at the sample size which has been calculated using the Slovin formula and knowing the minimum number required, namely 40 respondents. The results of the study stated that there was an influence between pregnant women's knowledge about preeclampsia and prevention of preeclampsia. This is proven by the results of the analysis of p value = 0.000 (p value < 0.05) indicating that there is a significant influence between knowledge of pregnant women and prevention of preeclampsia.